Knowledge management framework for Faculty of Computer Science & Information Technology University of Malaya / Vijayan Venggadasallam - Vijayan, Venggadasallam (2004)
Knowledge management is not one single discipline. Rather, it is integration of numerous endeavors and fields of study. This research proposes a conceptual framework for knowledge management implementation at Faculty of Computer Science & Information Technology. The framework focuses on the importance of aligning the knowledge management strategy with the objectives or goals of the faculty. Basically, the framework consists of three main interlinked components: Organization (Faculty), People, and Infrastructure and Processes. The culture for implementing knowledge management is also dealt with. Furthermore, the framework recommends a holistic approach to managing knowledge. The proposed framework can be useful for this faculty to improve their ability to learn and adapt to changing environments. This research also emphases the computer-based systems can bring benefit in knowledge-based activities by using it to support the development and communication of human meaning. Finally, it is hoped that this research can contribute for the successful of future knowledge management implementation at this faculty.